2007
DOI: 10.1242/jeb.001925
|View full text |Cite
|
Sign up to set email alerts
|

Tribute to P. L. Lutz: cardiac performance and cardiovascular regulation during anoxia/hypoxia in freshwater turtles

Abstract: SUMMARY Freshwater turtles overwintering in ice-covered ponds in North America may be exposed to prolonged anoxia, and survive this hostile environment by metabolic depression. Here, we review their cardiovascular function and regulation, with particular emphasis on the factors limiting cardiac performance. The pronounced anoxia tolerance of the turtle heart is based on the ability to match energy consumption with the low anaerobic ATP production during anoxia. Together with a well-developed tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 101 publications
1
36
0
Order By: Relevance
“…Also, the lower heart rate in the present study is probably due to long breath-holds and high vagal tone, which indicates that the turtles were undisturbed and unstressed. Consistent with previous studies on turtles, anoxia caused significant reductions in heart rate and systemic arterial pressure (Hicks and Wang, 1998;Stecyk et al, 2004;Overgaard et al, 2007). Although blood flow was not measured in the present study, earlier studies at a similar temperature have demonstrated a peripheral vasoconstriction mediated by increased sympathetic tone on the systemic vessels (Stecyk et al, 2004), and that H 2 S generation may play some role, particularly at low temperatures (Stecyk et al, 2010).…”
Section: Cardiovascular Changes and Role Of Circulating No Metabolitesupporting
confidence: 90%
See 2 more Smart Citations
“…Also, the lower heart rate in the present study is probably due to long breath-holds and high vagal tone, which indicates that the turtles were undisturbed and unstressed. Consistent with previous studies on turtles, anoxia caused significant reductions in heart rate and systemic arterial pressure (Hicks and Wang, 1998;Stecyk et al, 2004;Overgaard et al, 2007). Although blood flow was not measured in the present study, earlier studies at a similar temperature have demonstrated a peripheral vasoconstriction mediated by increased sympathetic tone on the systemic vessels (Stecyk et al, 2004), and that H 2 S generation may play some role, particularly at low temperatures (Stecyk et al, 2010).…”
Section: Cardiovascular Changes and Role Of Circulating No Metabolitesupporting
confidence: 90%
“…Hicks and Wang, 1998; Stecyk et al, 2004;Overgaard et al, 2007). Large variation in heart rates amongst studies can be expected due to the pronounced tachycardia during pulmonary ventilation and the bradycardia associated with apnoea (e.g.…”
Section: Cardiovascular Changes and Role Of Circulating No Metabolitementioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies about respiratory system related to the diving strategy of some turtle species. They are dominated by studies on sea turtle [8][9][10][11][12][13], while the studies on softshells turtle and terrapene only on turtles' species from America and other regions except South East Asia [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Acute systemic asphyxia causes profound electrophysiologic dysfunction in the conductive system of the myocardium, which affects sinus node function, the atrioventricular (AV) node refractory period [14][15][16], PQ interval [17][18][19], distribution of refractory periods [19], and changes in heart rate [20,21], as well as the threshold for ventricular arrhythmias [22].…”
Section: Introductionmentioning
confidence: 99%